1998
DOI: 10.1152/jappl.1998.84.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of allergic airway responses by inhaled low-molecular-weight heparins: molecular-weight dependence

Abstract: Inhaled heparin prevents antigen-induced bronchoconstriction and inhibits anti-immunoglobulin E-mediated mast cell degranulation. We hypothesized that the antiallergic action of heparin may be molecular weight dependent. Therefore, we studied the effects of three different low-molecular-weight fractions of heparin [medium-, low-, and ultralow-molecular-weight heparin (MMWH, LMWH, ULMWH, respectively)] on the antigen-induced acute bronchoconstrictor response (ABR) and airway hyperresponsiveness (AHR) in allergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…22 On the other hand, inhaled unfractionated heparin and low-molecular-weight heparins inhibited antigen-induced histamine release in bronchoalveolar lavage fluid by 81% and 75%; thus, the inhibitory effects of unfractionated heparin and fractionated heparins on histamine release are not strictly molecular weight-dependent. 23 In our current study, the unfractionated heparin was used mainly because we have shown previously that inhaled unfractionated heparin attenuated the airway response to AMP bronchial provocation.…”
Section: Discussionmentioning
confidence: 95%
“…22 On the other hand, inhaled unfractionated heparin and low-molecular-weight heparins inhibited antigen-induced histamine release in bronchoalveolar lavage fluid by 81% and 75%; thus, the inhibitory effects of unfractionated heparin and fractionated heparins on histamine release are not strictly molecular weight-dependent. 23 In our current study, the unfractionated heparin was used mainly because we have shown previously that inhaled unfractionated heparin attenuated the airway response to AMP bronchial provocation.…”
Section: Discussionmentioning
confidence: 95%
“…It was found that mainly heparin of low MW modifies the antigen–induced airway response and that heparin of ultra low MW is the most effective fraction in the prevention of allergic bronchoconstriction and airway hyperresponsiveness [33, 34, 35]. An influence on immunologically active cells, such as mast cells, basophils, eosinophils, endothelial cells, cell migration, as well as IL–4, IL–5 and TNF–α has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies showed biologic actions of heparin are molecular weight-dependent [6], [7]. The anti-allergic activity of heparin fractions shows an inverse relationship to the molecular weight [8]. Enoxaparin, a low-molecular-weight (lmw) heparin, is an anticoagulant used to prevent and treat deep vein thrombosis or pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%